Non-replication of an association of CTNNBL1 polymorphisms and obesity in a population of Central European ancestry - Wichmann H-Erich; Illig Thomas; Heid Iris M; Grallert Harald; Friedel Susann; Müller Timo D; Scherag André; Greene Brandon; Vogel Carla IG; Schäfer Helmut; Hebebrand Johannes; Hinney Anke (BMC, 2009)
Abstract Background A recent genome-wide association (GWA) study of U.S. Caucasians suggested that eight single nucleotide polymorphisms (SNPs) in CTNNBL1 are associated with obesity and increased fat mass. We analysed the respective SNPs in data from our previously published GWA for early onset obesity (case-control design), in GWA data from a population-based cohort of adults, and in an independent family-based obesity study. We investigated whether variants in CTNNBL1 (including rs6013029) and in three other genes (SH3PXD2B, SLIT3 and FLJ42133,) were associated with obesity. Methods The GWA studies were carried out using Affymetrix® SNP Chips with approximately 500,000 markers each. In the families, SNP rs6013029 was genotyped using the TaqMan® allelic discrimination assay. The German case-control GWA included 487 extremely obese children and adolescents and 442 healthy lean individuals. The adult GWA included 1,644 individuals from a German population-based study (KORA). The 775 independent German families consisted of extremely obese children and adolescents and their parents. Results We found no evidence for an association of the reported variants in CTNNBL1 with early onset obesity or increased BMI. Further, in our family-based study we found no evidence for over-transmission of the rs6013029 risk-allele T to obese children. Additionally, we found no evidence for an association of SH3PXD2B, SLIT3 and FLJ42133 variants in our two GWA samples. Conclusion We detected no confirmation of the recent association of variants in CTNNBL1 with obesity in a population of Central European ancestry.